BJOG Editor's Choice. (April 2016) - Chien, Patrick
Abstract : Deputy Editor‐in‐Chief, Dr Patrick Chien, discusses his top articles from this issue in an audio podcast availablehttps://soundcloud.com/bjog/april-editors-choice-2016